(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
The new edition of ISO 8529 series reduced from 4 to 3 standard neutron reference field. Recent studies have highlighted the increasing importance of characterizing neutron source spectra at different energies to obtain appropriate fluence-to-dose-equivalent conversion coefficient. This study presents the determination of neutron energy fluency from a free and moderated 252Cf (120 µg) source placed within spheres of different diameters containing distilled water. The spectrum determination is based on both Monte Carlo simulations and experimental measurements with Bonner Sphere Spectrometer (BSS) of multiple diameters: 5.08 cm (2"), 7.62 cm (3”), 12.70 cm (5”), 20.32 cm (8”), 25.40 cm (10”), and 30.48 cm (12”). The aim was to characterize the new water-moderated spectra, obtaining reference values for operational quantities that represent realistic radiation fields for testing, calibrating, and irradiation of personal dosimetry and survey meters.